Writings on Love in the English Middle Ages
XIII, 204 p.
Keywords: This is a set of essays from many of the leading scholars in the world of medieval studies, which addresses a wide diversity of texts and genres and their diverse perspectives on love. Attention is given to interaction between English writings and putative continental and international influences, with particular emphasis on the works of Chaucer.